Plants for Immunity and Conservation Strategies - Mishra, Manoj Kumar; Kumari, Nishi (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited book deals with medicinal plants (herbs and trees) used in critical diseases which contain a rich resource of bioactive compounds that can be used as immuno-boosters or recommended for therapeutic values. Each chapter provides the basic information such as taxonomic description, occurrence and importance of medicinal plants. The detail description of major bioactive compounds in medicinal plants, their chemical nature and clear flow chart of biosynthesis are important steps in this book. This book also includes conservation strategy both in-situ and ex-situ, which assist the research and academic purpose. This book is of interest to national and international researchers, teacher's, pharma scientists, and policymakers. Also, the book serves as additional reading material for both undergraduate and graduate students of pharma and agriculture in the world.
Chapter 1. A Literature update on strategies for harnessing and conserving the bioactive phytochemicals from Tinospora cordifolia: current status, challenges and future prospects -- Chapter 2. Medicinally important phytoconstituents and conservation strategies of neem: A critical overview -- Chapter 3. An Insight into Coptis teeta Wall. an endangered medicinal plant and their conservation strategies -- Chapter 4. Strategies for Conservation and Production of Bioactive Phytoconstituents in Commercially Important Ocimum Species: A Review -- Chapter 5. Studies of natural product synthesis of Withania somnifera and their conservation strategy through in-vitro method -- Chapter 6. In vitro studies in Andrographis paniculata pertaining to Andrographolides accumulation. Chapter 7. Identification of bioactive compounds in Berberis species and in-vitro propagation for conservation and quality -- Chapter 8. Bioactive compounds in Solanum viarum: medicinal properties, in vitro propagation, and conservation -- Chapter 9. Biosynthesis of essential oils in Artemisia species and conservation through in vitro propagation -- Chapter 10. Immunostimulatory properties of Echinacea purpurea and conservation strategy -- Chapter 11. An insight of phytochemicals of Satavari (Asparagus racemosus) -- Chapter 12. Ex-situ conservation of Shatavari (Asparagus racemosus). Chapter 13. Recent developments in natural compounds of Guggul and production of plant material for conservation and pharmaceutical demand Commiphora wightii (Arn.) Bhandari -- Chapter 14. Assessment of economically and medicinally important plant resources in Sangla Valley region of Indian Himalaya -- Chapter 15. Ethnomedicinal Pertinence and Antibacterial Prospective of Himalayan Medicinal Plants of Uttarakhand in India -- Chapter 16. An immune modulator constituent in Mucuna pruriens L. (DC) and biotechnological approach for conservation -- Chapter 17. In vitro cultures: Challenges and limitations.
Keywords: Plant biotechnology; Botanical chemistry; Plants -- Disease and pest resistance; Plant Biotechnology; Plant Biochemistry; Plant Immunity